NUTRITIVE EVALUATION OF SELECTED ENERGY, PROTEIN AND FIBRE FEEDSTUFFS - Eche, B. S.; Doma, U. D.; Abubakar, M. M. (Nigerian Journal of Agriculture and Agricultural Technology, 2025)
The study was conducted to evaluate the proximate composition of selected energy, protein (plant and animal origin) and fibre feedstuffs for poultry feeding. The feedstuffs were obtained from Muda Lawal market in Bauchi town and were cleaned, milled and screened to fine particle size of less than 250µm. All the feedstuffs were subjected to proximate analysis for the determination of dry matter, crude protein, ether extract, crude fibre and ash while nitrogen free extract and metabolizable energy were computed using mathematical relationships. The results revealed that energy sources are generally higher in metabolizable energy with values ranging from 2830.50-3359.97kcal/kg in Dauro millet and yellow maize, respectively which were however, mostly low in crude protein (8.64 vs 11.67%). Of the plant protein sources, groundnut cake contains the highest crude protein (43.21%) closely followed by full fat soya bean (41.68%). The lowest crude protein was obtained on Bambara nut (22.61%). Blood meal contains the highest protein (70.62%) followed by industrial fish meal (64.55%) and local fish meal (59.19%). For fibre feedstuff, wheat offal contained the highest crude protein (16.24%) while the lowest value of 6.49% was obtained in rice offal. Rice offal had the highest crude fibre value of 31.23%. The local maize offal and millet offal are richer in energy (2250vs2275kcal/kg). It recommended that major ingredients of feeds (energy, protein, fibre) must be analyzed for nutrients, availability and density before incorporation into poultry feeds.